Temperate Forest Floors: Ecosystem Hubs in Transition? - Friederike Lang; Jörg Prietzel; Frank Hagedorn; Klaus Kaiser; Stefanie Schulz; Mathias Mayer; Lars Vesterdal; Jürgen Bauhus; Maï Bergmann; Sebastian Bibinger; Martin I. Bidartondo; Jingxuan Olivia Chen; et al. (Global Change Biology, 2026)
The forest floor (FF) plays a key role in carbon, nutrient, and water cycling. It is the biologically most active compartment of forest soils, highly responsive to environmental conditions. Yet, its response to current changes in environmental conditions and forest management is understudied. Temperate forests are among the best studied ecosystems globally, providing the necessary ecological and biogeochemical background information to assess FF changes. Here, we focus on identifying existing knowledge and gaps in our understanding of the functioning of the FF. Interactions between FF biota and abiotic FF components show multifactorial dependencies with environmental conditions and drive FF turnover. Vice versa, the turnover of FF regulates carbon, nutrient, and water cycling. With slow litter decomposition and limited bioturbation, organic matter accumulates, nutrients cycle tightly within the FF, and water passes through this layer partly along preferential pathways. With rapid litter decomposition and intense bioturbation, FF accumulation is little, the mineral soil is the main nexus for plant nutrient uptake and organic matter transformation, and water infiltrates the mineral soil more homogeneously. The interconnectedness with the adjacent ecosystem compartments is a crucial feature of the FF, feeding back to its functioning and making it a central hub of forest processes. The FF morphology reflects these processes and therefore has untapped potential as an indicator of soil and ecosystem health. Under forest change, the FF might lose its functionality, with negative impacts on nutrient provision, water storage, and carbon sequestration. Consequences for forest growth could be strong and even detrimental. Hence, improved knowledge of FF characteristics and their linkages to mineral soils and aboveground ecosystem compartments is crucial for assessing forest resilience to progressing environmental changes.

Shallow evolutionary divergence in the Antarctic notothenioid genus Harpagifer across the Southern Ocean - Nicolas I. Segovia; Valentina Bernal-Durán; Javier Naretto; Mathias Hüne; Thomas Saucède; Guillaume Schwob; Paul Brickle; Simon A. Morley; Ofer Gon; Tshoanelo Miya; Karin Gérard; Pilar A. Haye; et al. (Hydrobiologia, 2026)

Impact of perfluorooctanesulfonic acid (PFOS) on phytoplankton community and physiological responses - Suleiman Dauda; Yillek Simon Gotan; Sadiya Awala Samuel; Adriana Sturion Lorenzi; Zainab Abdullahi Ibrahim; Dora Nguemo Iortsuun; Mathias Ahii Chia (Aquatic Ecology, 2026)
Perfluorooctanesulfonic acid (PFOS), a persistent and bioaccumulative substance, has emerged as a major environmental contaminant of global concern. PFOS, widely used in industry and consumer products, is common in aquatic ecosystems and may harm primary producers like phytoplankton, though its effects on their community structure and physiology remain unclear. Here, we investigated the impact of PFOS on freshwater physicochemical parameters, phytoplankton community dynamics, biochemical composition, and oxidative stress responses in a mesocosm experiment over a 28-day period. The water quality indicators generally were unaltered by PFOS exposure, but phosphate levels decreased initially in the control. Phytoplankton biomass (cell density) decreased at 10 µg L −1 and 10 mg L −1 PFOS exposures. Phytoplankton species richness, Shannon, and Simpson diversity indices declined at 10 mg L −1 , with communities at this concentration becoming distinctly different from the control and lower PFOS treatments by day 28. This shift in community structure was primarily driven by taxa such as Chlorogonium sp. and Microcystis aeruginosa , which contributed strongly to the observed compositional dissimilarity. Proteins content in the phytoplankton increased under PFOS exposure, peaking on day 21. In contrast, carbohydrate and lipid contents were reduced under PFOS relative to the control. PFOS exposure elevated glutathione-S-transferase activity, malondialdehyde, and hydrogen peroxide levels, whereas peroxidase activity was reduced. The phytoplankton biomass and lipids were positively associated, while oxidative stress markers were closely linked with high PFOS concentrations. Overall, these results highlight that PFOS exposure suppressed phytoplankton biomass, altered their community composition, and induced oxidative stress and metabolic shift at higher concentrations, highlighting its potential ecological risk in freshwater systems.

Impact of prenatal LPS on sepsis-related neurobiological outcomes - Fernanda Frederico Gava; Larissa Joaquim; Naila Maciel; Khiany Mathias; Richard Simon Machado; Brenno Farias; Thainá Cidreira; Sabini Abrahão; Beatriz Steiner Cardoso; Marina Goulart; Carolina Giassi Alano; Rafaela Tezza Matiola; et al. (Metabolic Brain Disease, 2026)
Background early-life challenges during the prenatal period can induce persistent neurological alterations. The immature innate immune system exhibits plasticity, and appropriately timed stimuli may shape immune responses into adulthood. Objective to investigate whether prenatal exposure to lipopolysaccharide (LPS) modulates brain alterations after sepsis in adult offspring of both sexes. Methods pregnant Wistar rats received an intraperitoneal injection of LPS (100 µg/kg) on gestational day 9.5. In adulthood, offspring underwent cecal ligation and perforation (CLP) or sham surgery, generating four groups: sal+sham, LPS+sham, sal + CLP, and LPS + CLP. Survival was monitored, and behavioral assessments (open field habituation and forced swim test) were performed 10 days post-surgery. Brain regions (cortex, prefrontal cortex, hippocampus) were analyzed for cytokine levels, myeloperoxidase (MPO) activity, nitrite/nitrate (N/N) concentrations, oxidative damage, catalase (CAT) activity, and mitochondrial respiratory chain complex activities (I, II, IV). Results prenatal LPS improved survival, enhanced habituation memory (both sexes), and reduced depressive-like behavior (females). It increased IL-10 across brain regions and IL-6 in the male hippocampus, while reducing N/N in the female prefrontal cortex and hippocampus. Oxidative damage was attenuated, with reduced lipid peroxidation in the male prefrontal cortex and decreased protein carbonylation in both sexes. CAT activity increased in the male cortex and hippocampus. Prenatal LPS preserved mitochondrial complex I and IV activities in the male hippocampus, complex I in cortex and prefrontal cortex, and complex II in the female prefrontal cortex. Conclusion prenatal immune challenge with LPS confers sex-dependent neuroprotective effects, reducing inflammation, oxidative damage, and mitochondrial dysfunction induced by severe sepsis in adult offspring. Graphical Abstract

A theoretical appraisal of the GR4J rainfall-runoff modelling framework - Simon A. Mathias; Cyril Thébault; Andrew Ireson (Journal of Hydrology, 2026)

Impact of Diabetes on Oxidative Stress, Mitochondrial Function, and Neurological Outcomes Following Ischemic Stroke: A Sex-Based Experimental Analysis - Richard Simon Machado; Khiany Mathias; Cristiane Coral; David dos Santos; Sandra Regina Santana Aguiar Bonfante; Solange de Souza Stork; Anita Dal Bó Tiscoski; Victor Duílio Antunes Maragno; Alberto Martins Silva; Henrique Mautone Gomes; Isabela da Silva Lemos; Luana dos Reis Possa; et al. (Molecular Neurobiology, 2026)

Emerging Roles of Meningeal Lymphatic Vessels in Ischemic Stroke - Richard Simon Machado; Khiany Mathias; Larissa Joaquim; Maiara de Aguiar da Costa; Anita Tiscoski; Cinara Ludvig Gonçalves; Gislaine Tezza Rezin; Fabricia Petronilho (Molecular Neurobiology, 2025)

Submarine groundwater discharge into a temperate tidal basin: Mapping and characterization by a multi-method and multi-scale approach - Ercan Erkul; Tina Wunderlich; Dennis Wilken; Jan Igel; Mike Müller-Petke; Mathias Ronczka; Tobias Splith; Simon Fischer; Benjamin Gilfedder; Michael Ernst Böttcher; Cátia M. Ehlert von Ahn; Ralf Gründling; et al. (Estuarine, Coastal and Shelf Science, 2025)

Impact of decarbonisation on water availability in the UK - Simon Mathias; Andrew Smallbone; Fred Worrall; Nigel Corfield; Tony March; Robert Barker (Sustainable Water Resources Management, 2025)
The UK aims to capture and store 20–30 Mt $$\hbox {CO}_{2}\hbox {e}$$ annually and produce 10 GW of low-carbon hydrogen by 2030. This study evaluates the potential water resource impacts of these decarbonisation efforts across five UK water company regions: Anglian Water, Northumbrian Water, Severn Trent Water, United Utilities, and Yorkshire Water. Projected $$\hbox {CO}_{2}$$ capture and hydrogen production rates are obtained from publicly available project databases and converted into associated water withdrawal rates using specific water intensity factors (SWIF) for $$\hbox {CO}_{2}$$ capture, blue hydrogen production and green hydrogen production. These SWIFs are derived through a combination of literature review and Integrated Environmental Control Model (IECM) simulations. Parameter uncertainty and project start-time uncertainty are incorporated using Monte Carlo simulation. Water withdrawals are spatially allocated to water company regions and compared with existing regional water availability forecasts derived from UK Water Resources Management Plans (WRMP24). Results indicate that additional water demand due to decarbonisation in the UK could reach 860 ± 150 ML/day by 2050, driven equally by $$\hbox {CO}_{2}$$ capture, blue hydrogen production, and green hydrogen production. Regional impacts vary, with significant deficits projected for Anglian Water and United Utilities by 2030 and for Yorkshire Water by 2040, while other regions are expected to maintain surplus capacity. Recommendations include adopting technologies with lower SWIF values, enhancing collaboration between decarbonisation project managers and water companies, establishing regional desalination hubs, redistributing water resources, and implementing adaptive water management strategies to ensure sustainable resource use.

A new approach to haemoglobin oxygen affinity research at high altitude: Determination of haemoglobin oxygen dissociation curves and 2,3-bisphosphoglycerate in an experimental human crossover hypoxic chamber study - Simon Woyke; Herbert Oberacher; David Plunser; Christoph Siebenmann; Rachel Turner; Ivo B. Regli; Maja Schlittler; Giacomo Strapazzon; Hermann Brugger; Mathias Ströhle; Thomas Haller; Hannes Gatterer (European Journal of Applied Physiology, 2025)
Purpose During rapid exposure to hypobaric hypoxia (HH), arterial oxygen tension and haemoglobin oxygen saturation decrease. The oxygen dissociation curve (ODC) describes the relationship of oxygen tension and haemoglobin oxygen saturation. Previous methods for ODC determination are mostly limited to standard conditions (40 mmHg PCO 2 , 37 °C), and measurements of 2,3-bisphosphoglycerate (2,3-BPG) and adenosine triphosphate (ATP) are omitted. This study aimed to investigate hypoxia-induced changes on the ODC in a strictly controlled hypobaric chamber setting utilising a novel method for ODC determination, incorporating innovative 2,3-BPG and ATP measurements. Methods In a randomised crossover design, ten healthy males completed two 4-day sojourns, one in HH (3,500 m) and one in normoxia (NX, 262 m). ODCs were determined from venous blood at 96 h using a highly customisable high-throughput microplate reader method. Haemoglobin half saturation pressure (P50) was measured for a standardised CO 2 tension of 40 mmHg (P50 st ) and individual end-tidal CO 2 tensions (P et CO 2 ) (P50 act ). 2,3-BPG and ATP were determined by liquid chromatography–tandem mass spectrometry. Results P50 st were increased in HH compared to NX but missed statistical significance (28.3 ± 2.0 mmHg vs. 26.8 ± 1.9 mmHg; p = 0.054), whilst P50 act was similar in HH and NX (26.4 ± 1.6 mmHg vs. 26.1 ± 2.7 mmHg; p = 0.360) despite reduced P et CO 2 (31.0 ± 2.1 mmHg vs. 38.4 ± 2.5 mmHg; p < 0.001). 2,3-BPG and pH were significantly increased in HH compared to NX (16.8 ± 1.6 µmol/gHb and 20.5 ± 1.1 µmol/gHb, p < 0.001; 7.36 ± 0.01 versus 7.39 ± 0.02, p < 0.001). Conclusion The 2,3-BPG increase after 96 h in HH compensates the effect of hypoxia-induced decrease in P et CO 2 /increase in pH on the ODC.

Full-spectrum Cannabis sativa extract enhances gut-peripheral organ integrity after experimental ischemic stroke - Solange de Souza Stork; Khiany Mathias; Fernanda Gava; Larissa Joaquim; David dos Santos; Anita Dal Bó Tiscoski; Sandra Bonfante; Yasmin Ribeiro Strickert; Richard Simon Machado; Helena Mafra Martins; Jéssica Schaefer Chaves; Jaqueline Generoso; et al. (Inflammopharmacology, 2025)

Ayahuasca Pretreatment Prevents Sepsis-Induced Anxiety-Like Behavior, Neuroinflammation, and Oxidative Stress, and Increases Brain-Derived Neurotrophic Factor - Rick Wilhiam de Camargo; Larissa Joaquim; Richard Simon Machado; Suelen de Souza Ramos; Lara Rodrigues da Rosa; Linério Ribeiro de Novais Junior; Khiany Mathias; Lara Maximiano; Yasmin Ribeiro Strickert; Rafael Nord; Maria Laura Gava; Eduarda Scarpari; et al. (Molecular Neurobiology, 2025)

Exploring NLRP3 Inhibition as a Key Modulator in Neonatal Hypoxic-Ischemic Brain Injury - Khiany Mathias; Richard Simon Machado; Taise Cardoso; Beatriz Naspolini; Josiane Prophiro; Fabricia Petronilho (NeuroMolecular Medicine, 2025)

Chitinase-3 Like-Protein-1 Signature in Neurological Disorders: Emphasis on Stroke - Khiany Mathias; Richard Simon Machado; Naíla Maciel Andrade; Natalia Piacentini; Carla Damasio Martins; Josiane Somariva Prophiro; Fabricia Petronilho (Journal of Molecular Neuroscience, 2025)

Evaluating scleral exposure in human eyes: a review of measurement methods, an exploration of reliability, and implications in behavioral experimental research - Mathias Boyer-Brosseau; Sébastien Hétu; Simon Rigoulot (Behavioral Ecology and Sociobiology, 2025)

Development of a fully automated slurry sampling introduction system for GF-AAS and its application for the determination of cadmium in different matrices - Charlie Tobias; Lennart Gehrenkemper; Thomas Bernstein; Sven Schlau; Fabian Simon; Mathias Röllig; Björn Meermann; Marcus von der Au (Analytica Chimica Acta, 2025)

The EnMAP spaceborne imaging spectroscopy mission: Initial scientific results two years after launch - Sabine Chabrillat; Saskia Foerster; Karl Segl; Alison Beamish; Maximilian Brell; Saeid Asadzadeh; Robert Milewski; Kathrin J. Ward; Arlena Brosinsky; Katrin Koch; Daniel Scheffler; Stephane Guillaso; et al. (Remote Sensing of Environment, 2024)

Oxidative stress and mitochondrial dysfunction contributes to postoperative cognitive dysfunction in elderly rats dependent on NLRP3 activation - Sandra Bonfante; Martins Back Netto; Aloir Neri de Oliveira Junior; Khiany Mathias; Richard Simon Machado; Larissa Joaquim; Taina Cidreira; Marina Goulart da Silva; Guilherme Cabreira Daros; Lucinéia Gainski Danielski; Fernanda Gava; Isabela da Silva Lemos; et al. (Metabolic Brain Disease, 2024)

The Blood-Cerebrospinal Fluid Barrier Dysfunction in Brain Disorders and Stroke: Why, How, What For? - Khiany Mathias; Richard Simon Machado; Taise Cardoso; Anita dal Bó Tiscoski; Natália Piacentini; Josiane Somariva Prophiro; Jaqueline Silva Generoso; Tatiana Barichello; Fabricia Petronilho (NeuroMolecular Medicine, 2024)

Integrating artificial intelligence with expert knowledge in global environmental assessments: opportunities, challenges and the way ahead - Veruska Muccione; Saeid Ashraf Vaghefi; Julia Bingler; Simon K. Allen; Mathias Kraus; Glen Gostlow; Tobias Wekhof; Chiara Colesanti-Senni; Dominik Stammbach; Jingwei Ni; Tobias Schimanski; Tingyu Yu; et al. (Regional Environmental Change, 2024)
With new cycles of global environmental assessments (GEAs) recently starting, including GEO-7 and IPCC AR7, there is increasing need for artificial intelligence (AI) to support in synthesising the rapidly growing body of evidence for authors and users of these assessments. In this article, we explore recent advances in AI and connect them to the different stages of GEAs showing how some processes can be automatised and streamlined. The meticulous and labour-intensive nature of GEAs serves as both a valuable strength and a challenge to staying pertinent and current in today’s era of urgency and the pursuit of the latest knowledge. Utilising AI tools for reviewing and synthesizing scientific literature holds the evident promise of substantially lessening the workload for experts and expediting the assessment process. This, in turn, could lead to more frequent report releases and a smoother integration of the latest scientific advancements into actionable measures. However, successful outcomes can only be achieved if domain experts co-develop and oversee the deployment of such tools together with AI researchers. Otherwise, these tools run the risk of producing inaccurate, incomplete, or misleading information with significant consequences. We demonstrate this through a few examples that compare recently deployed large language models (LLMs) based tools in their performance in capturing nuanced concepts in the context of the reports of the Intergovernmental Panel on Climate Change (IPCC). We recommend establishing ethical committees and organising dedicated expert meetings to develop best practice guidelines, ensuring responsible and transparent integration of AI into GEAs.

Two Film Approach to Continuum Scale Mixing and Dispersion with Equilibrium Bimolecular Reaction - Simon A. Mathias; Diogo Bolster; Sergii Veremieiev (Transport in Porous Media, 2024)
Reliable reactive transport models require careful separation of mixing and dispersion processes. Here we treat displacing and displaced fluids as two separate fluid phases and invoke Whitman’s classical two-film theory to model mass transfer between the two phases. We use experimental data from Gramling’s bimolecular reaction experiment to assess model performance. Gramling’s original model involved just three coupled PDEs. In this context, our new formulation leads to a set of seven coupled PDEs but only requires the specification of two extra parameters, associated with the mass transfer coefficient and its dependence on time. The two film mass transfer model provides a simple and theoretically based method for separating mixing from dispersion in Eulerian continuum-scale methods. The advantage of this approach over existing methods is that it enables the simulation of equilibrium chemical reactions without having to invoke unrealistically small reaction rate coefficients. The comparison with Gramling’s experimental data confirms that our proposed method is suitable for simulating realistic and complicated bimolecular reaction behaviour. However, further work is needed to explore alternative methods for avoiding the need of a time-dependent mass transfer rate coefficient.

Phase behaviour and structure formation of alginate-gelatin composite gels - Sabrina Bäther; Jasper Hartwig Seibt; Christoph Simon Hundschell; Jose C. Bonilla; Mathias Porsmose Clausen; Anja Maria Wagemans (Food Hydrocolloids, 2024)

Hyperoxia and brain: the link between necessity and injury from a molecular perspective - Richard Simon Machado; Khiany Mathias; Larissa Joaquim; Rafaella Willig de Quadros; Gislaine Tezza Rezin; Fabricia Petronilho (Neurotoxicity Research, 2024)

Human density impacts Nubian Flapshell turtle survival in Sub-Saharan Africa: Future conservation strategies - Gift Simon Demaya; Mathias Behangana; Fabio Petrozzi; Julia E. Fa; Luca Luiselli (Journal of Arid Environments, 2023)

A New Preparation Method for 3D Bio-composite Filament Manufacturing: a Study on the Effects of Ball Milling on the Cohesion/Adhesion of an Agave tequilana Bagasse/PLA Pellet Mixture - Mathias Salignon; Simon Gray; Timothy Rose; Adriana Encinas-Oropesa (Circular Economy and Sustainability, 2023)
This study created a composite polymer for 3D printing from agave by-product using mechanical alloying process. The cold milling technique used by the ball mill is a standard procedure to homogenize metallic mixtures. This paper reports results from a series of laboratory tests to create a homogeneous mixture that could be extruded into a printable filament mixture of agave bagasse fibres and PLA pellets by using the kinetic energy of a ball mill. PLA and agave bagasse mixtures in this study were ground several times using this principle; steel and ceramic balls were used to grind them. The results of the study showed that this principle can be effective on a polymer-based mixture; indeed, an adhesion between the pellets and the agave bagasse fibres was obtained. The results showed the different parameters that influence the mixture quality as the milling time, the ball material, the number of balls, the mixture concentration and the rotational speed. Optical and ESEM/EDX analyses have confirmed our expectations about cohesion between fibres pulverized in powder and pellet adhesion, where powder accumulation on all the surfaces was detected. The absence of powder penetration in the pellets allowed us to explain the losses obtained during the process and to find new solutions to reduce them. Proof-of-concept parts were 3D printed with agave bagasse/PLA filaments. Their printed quality can be compared to that of commercial filaments. These results offer new perspectives to reuse agricultural by-products to create composite filament with a chemical-free manufacturing process.

The EnMAP imaging spectroscopy mission towards operations - Tobias Storch; Hans-Peter Honold; Sabine Chabrillat; Martin Habermeyer; Paul Tucker; Maximilian Brell; Andreas Ohndorf; Katrin Wirth; Matthias Betz; Michael Kuchler; Helmut Mühle; Emiliano Carmona; et al. (Remote Sensing of Environment, 2023)

Targeted hydrolysis of native potato protein: A novel workflow for obtaining hydrolysates with improved interfacial properties - Simon Gregersen Echers; Ali Jafarpour; Betül Yesiltas; Pedro J. García-Moreno; Mathias Greve-Poulsen; Dennis K. Hansen; Charlotte Jacobsen; Michael Toft Overgaard; Egon Bech Hansen (Food Hydrocolloids, 2023)

Review of gene drive modelling and implications for risk assessment of gene drive organisms - Johannes L. Frieß; Carina R. Lalyer; Bernd Giese; Samson Simon; Mathias Otto (Ecological Modelling, 2023)

Revisiting Salvucci’s Semi-analytical Solution for Bare Soil Evaporation with New Consideration of Vapour Diffusion and Film Flow - Simon A. Mathias; Graham C. Sander; Jessica Leung; Samuel R. Newall (Transport in Porous Media, 2023)
Bare soil evaporation is controlled by a combination of capillary flow, vapour diffusion and film flow. Relevant analytical solutions mostly assume horizontal flow conditions and ignore gravitational effects. Salvucci (1997) provided a rare example of a semi-analytical solution for vertical bare soil evaporation. However, they did not explicitly represent vapour diffusion and film flow, which are likely to account for a significant proportion of total flow during vertical evaporation from soils. Vapour diffusion and film flow can be incorporated via Salvucci’s desorptivity parameter, which represents the proportionality constant relating Stage 2 cumulative evaporation to the square root of time under horizontal flow conditions. The objective of this article is to implement vapour diffusion and film flow within Salvucci’s semi-analytical solution and test its performance by comparison with isothermal numerical simulation and relevant experimental data. The following important conclusions are drawn. Analytical solutions that assume horizontal flow conditions are inadequate for understanding vertical evaporation problems because they overestimate evaporation rates and mostly predict vapour diffusion and film flow to be of negligible influence. Salvucci’s semi-analytical solution is effective at predicting the order-of-magnitude reduction in evaporation caused by gravitational effects. However, it is unable to identify the correct importance of vapour diffusion and film flow because these processes can only be represented through its desorptivity parameter.

Impact of land cover, rainfall and topography on flood risk in West Java - Rahmawati Rahayu; Simon A. Mathias; Sim Reaney; Gianni Vesuviano; Rusmawan Suwarman; Agus M. Ramdhan (Natural Hazards, 2023)
Flooding represents around 32% of total disasters in Indonesia and disproportionately affects the poorest of communities. The objective of this study was to determine significant statistical differences, in terms of river catchment characteristics, between regions in West Java that reported suffering from flood disasters and those that did not. Catchment characteristics considered included various statistical measures of topography, land-use, soil-type, meteorology and river flow rates. West Java comprises 154 level 9 HydroSHEDS sub-basin regions. We split these regions into those where flood disasters were reported and those where they were not, for the period of 2009 to 2013. Rainfall statistics were derived using the CHIRPS gridded precipitation data package. Statistical estimates of river flow rates, applicable to ungauged catchments, were derived from regionalisation relationships obtained by stepwise linear regression with river flow data from 70 West Javanese gauging stations. We used Kolmogorov–Smirnov tests to identify catchment characteristics that exhibit significant statistical differences between the two sets of regions. Median annual maximum river flow rate (AMRFR) was found to be positively correlated with plantation cover. Reducing plantation land cover from 20 to 10% was found to lead to a modelled 38% reduction in median AMRFR. AMRFR with return periods greater than 10 years were found to be negatively correlated with wetland farming land cover, suggesting that rice paddies play an important role in attenuating extreme river flow events. Nevertheless, the Kolmogorov–Smirnov tests revealed that built land cover is the most important factor defining whether or not an area is likely to report flood disasters in West Java. This is presumably because the more built land cover, the more people available to experience and report flood disasters. Our findings also suggest that more research is needed to understand the important role of plantation cover in aggravating median annual maximum river flow rates and wetland farming cover in mitigating extreme river flow events.

Toward a forest biomass reference measurement system for remote sensing applications - Nicolas Labrière; Stuart J. Davies; Mathias I. Disney; Laura I. Duncanson; Martin Herold; Simon L. Lewis; Oliver L. Phillips; Shaun Quegan; Sassan S. Saatchi; Dmitry G. Schepaschenko; Klaus Scipal; Plinio Sist; et al. (Global Change Biology, 2023)
Forests contribute to climate change mitigation through carbon storage and uptake, but the extent to which this carbon pool varies in space and time is still poorly known. Several Earth Observation missions have been specifically designed to address this issue, for example, NASA's GEDI, NASA‐ISRO's NISAR and ESA's BIOMASS. Yet, all these missions' products require independent and consistent validation. A permanent, global, in situ, site‐based forest biomass reference measurement system relying on ground data of the highest possible quality is therefore needed. Here, we have assembled a list of almost 200 high‐quality sites through an in‐depth review of the literature and expert knowledge. In this study, we explore how representative these sites are in terms of their coverage of environmental conditions, geographical space and biomass‐related forest structure, compared to those experienced by forests worldwide. This work also aims at identifying which sites are the most representative, and where to invest to improve the representativeness of the proposed system. We show that the environmental coverage of the system does not seem to improve after at least the 175 most representative sites are included, but geographical and structural coverages continue to improve as more sites are added. We highlight the areas of poor environmental, geographical, or structural coverage, including, but not limited to, Canada, the western half of the USA, Mexico, Patagonia, Angola, Zambia, eastern Russia, and tropical and subtropical highlands (e.g. in Colombia, the Himalayas, Borneo, Papua). For the proposed system to succeed, we stress that (1) data must be collected and processed applying the same standards across all countries and continents; (2) system establishment and management must be inclusive and equitable, with careful consideration of working conditions; and (3) training and site partner involvement in downstream activities should be mandatory.

Agriculture intensity and landscape configuration influence the spatial use of wildcats across Europe - Héctor Ruiz-Villar; Matteo Luca Bastianelli; Marco Heurich; Stefano Anile; Francisco Díaz-Ruiz; Pablo Ferreras; Malte Götz; Mathias Herrmann; Saskia Jerosch; Fernando Jubete; José María López-Martín; Pedro Monterroso; et al. (Biological Conservation, 2023)

Lung-Brain Crosstalk in Sepsis: Protective Effect of Prophylactic Physical Exercise Against Inflammation and Oxidative Stress in Rats - Amanda Della Giustina; Judite Filgueiras Rodrigues; Erick Bagio; Sandra Bonfante; Larissa Joaquim; Graciela Zarbato; Solange Stork; Richard Simon Machado; Mariana Pereira de Souza Goldim; Lucinéia Gainski Danielski; Khiany Mathias; Carlos Dacoregio; et al. (Molecular Neurobiology, 2022)

Microbial Growth and Organic Matter Cycling in the Pacific Ocean Along a Latitudinal Transect Between Subarctic and Subantarctic Waters - Helge-Ansgar Giebel; Carol Arnosti; Thomas H. Badewien; Insa Bakenhus; John Paul Balmonte; Sara Billerbeck; Leon Dlugosch; Rohan Henkel; Birgit Kuerzel; Jens Meyerjürgens; Felix Milke; Daniela Voss; et al. (Frontiers in Marine Science, 2021)
The Pacific Ocean constitutes about half of the global oceans and thus microbial processes in this ocean have a large impact on global elemental cycles. Despite several intensely studied regions large areas are still greatly understudied regarding microbial activities, organic matter cycling and biogeography. Refined information about these features is most important to better understand the significance of this ocean for global biogeochemical and elemental cycles. Therefore we investigated a suite of microbial and geochemical variables along a transect from the subantarctic to the subarctic Pacific in the upper 200 m of the water column. The aim was to quantify rates of organic matter processing, identify potential controlling factors and prokaryotic key players. The assessed variables included abundance of heterotrophic prokaryotes and cyanobacteria, heterotrophic prokaryotic production (HPP), turnover rate constants of amino acids, glucose, and acetate, leucine aminopeptidase and β-glucosidase activities, and the composition of the bacterial community by fluorescence in situ hybridization (FISH). The additional quantification of nitrate, dissolved amino acids and carbohydrates, chlorophyll a , particulate organic carbon and nitrogen (POC, PON) provided a rich environmental context. The oligotrophic gyres exhibited the lowest prokaryotic abundances, rates of HPP and substrate turnover. Low nucleic acid prokaryotes dominated in these gyres, whereas in temperate and subpolar regions further north and south, high nucleic acid prokaryotes dominated. Turnover rate constants of glucose and acetate, as well as leucine aminopeptidase activity, increased from (sub)tropical toward the subpolar regions. In contrast, HPP and bulk growth rates were highest near the equatorial upwelling and lowest in the central gyres and subpolar regions. The SAR11 clade, the Roseobacter group and Flavobacteria constituted the majority of the prokaryotic communities. Vertical profiles of the biogeochemical and microbial variables markedly differed among the different regions and showed close covariations of the microbial variables and chlorophyll a , POC and PON. The results show that hydrographic, microbial, and biogeochemical properties exhibited distinct patterns reflecting the biogeographic provinces along the transect. The microbial variables assessed contribute to a better and refined understanding of the scales of microbial organic matter processing in large areas of the epipelagic Pacific beyond its well-studied regions.

Biochar as multi-purpose sustainable technology: experiences from projects in Tanzania - Anders Hansson; Simon Haikola; Mathias Fridahl; Pius Yanda; Edmund Mabhuye; Noah Pauline (Environment, Development and Sustainability, 2021)
Biochar was recently included as a promising negative emissions technology (NET) in the Special Report on Global Warming of 1.5 °C published by the Intergovernmental Panel on Climate Change. Unlike other NETs, it can potentially be used to mitigate global climate change while adding to local resilience in countries highly exposed and sensitive to impacts of climate change, such as least-developed countries (LDCs). The study is as an empirical contribution to the, as of yet, underdeveloped literature on deployment of negative emissions technologies in LDCs in general and on biochar use in developing countries and LDCs specifically. Nine historical and existing biochar projects in Tanzania are mapped in order to analyse problems, goals and common trade-offs associated with small- to medium-scale biochar production in LDCs. The mapping is based on a literature and document study, interviews with project actors, and on-site visits to biochar projects during 2019. The paper gives support to the observation made in the biochar literature that while biochar has many potential socio-economic and environmental benefits, combining them in one single project is difficult. It is concluded that implementing biochar projects in Tanzania will likely involve trade-offs between the development and subsistence strategies and needs of local communities, the motivational forces of different project participants, and the uneven regulatory capacity of the state. We end by reflecting on the use of biochar projects to offset carbon emissions made elsewhere.

A Novel Hybrid Membrane VAD as First Step Toward Hemocompatible Blood Propulsion - Aldo Ferrari; Costanza Giampietro; Björn Bachmann; Laura Bernardi; Deon Bezuidenhhout; Paolo Ermanni; Raoul Hopf; Sarah Kitz; Gerald Kress; Christian Loosli; Vita Marina; Mirko Meboldt; et al. (Annals of Biomedical Engineering, 2021)
Heart failure is a raising cause of mortality. Heart transplantation and ventricular assist device (VAD) support represent the only available lifelines for end stage disease. In the context of donor organ shortage, the future role of VAD as destination therapy is emerging. Yet, major drawbacks are connected to the long-term implantation of current devices. Poor VAD hemocompatibility exposes the patient to life-threatening events, including haemorrhagic syndromes and thrombosis. Here, we introduce a new concept of artificial support, the Hybrid Membrane VAD, as a first-of-its-kind pump prototype enabling physiological blood propulsion through the cyclic actuation of a hyperelastic membrane, enabling the protection from the thrombogenic interaction between blood and the implant materials. The centre of the luminal membrane surface displays a rationally-developed surface topography interfering with flow to support a living endothelium. The precast cell layer survives to a range of dynamically changing pump actuating conditions i.e., actuation frequency from 1 to 4 Hz, stroke volume from 12 to 30 mL, and support duration up to 313 min, which are tested both in vitro and in vivo , ensuring the full retention of tissue integrity and connectivity under challenging conditions. In summary, the presented results constitute a proof of principle for the Hybrid Membrane VAD concept and represent the basis for its future development towards clinical validation.

Preconditions for bioenergy with carbon capture and storage (BECCS) in sub-Saharan Africa: the case of Tanzania - Anders Hansson; Mathias Fridahl; Simon Haikola; Pius Yanda; Noah Pauline; Edmund Mabhuye (Environment, Development and Sustainability, 2020)
Most mitigation scenarios compatible with a likely change of holding global warming well below 2 °C rely on negative emissions technologies (NETs). According to the integrated assessment models (IAMs) used to produce mitigation scenarios for the IPCC reports, the NET with the greatest potential to achieve negative emissions is bioenergy with carbon capture and storage (BECCS). Crucial questions arise about where the enormous quantities of biomass needed according to the IAM scenarios could feasibly be produced in a sustainable manner. Africa is attractive in the context of BECCS because of large areas that could contribute biomass energy and indications of substantial underground CO 2 storage capacities. However, estimates of large biomass availability in Africa are usually based on highly aggregated datasets, and only a few studies explore future challenges or barriers for BECCS in any detail. Based on previous research and literature, this paper analyses the pre-conditions for BECCS in Tanzania by studying what we argue are the applications of BECCS, or the components of the BECCS chain, that are most feasible in the country, namely (1) as applied to domestic sugarcane-based energy production (bioethanol), and (2) with Tanzania in a producer and re-growth role in an international BECCS chain, supplying biomass or biofuels for export to developed countries. The review reveals that a prerequisite for both options is either the existence of a functional market for emissions trading and selling, making negative emissions a viable commercial investment, or sustained investment through aid programmes. Also, historically, an important barrier to the development of production capacity of liquid biofuels for export purposes has been given by ethical dilemmas following in the wake of demand for land to facilitate production of biomass, such as sugarcane and jatropha. In these cases, conflicts over access to land and mismanagement have been more of a rule than an exception. Increased production volumes of solid biomass for export to operations that demand bioenergy, be it with or without a CCS component, is likely to give rise to similar conflicts. While BECCS may well play an important role in reducing emissions in countries with high capacity to act combined with existing large point sources of biogenic CO 2 emissions, it seems prudent to proceed with utmost caution when implicating BECCS deployment in least developed countries, like Tanzania.The paper argues that negative BECCS-related emissions from Tanzania should not be assumed in global climate mitigation scenarios.

Old growth Afrotropical forests critical for maintaining forest carbon - John R. Poulsen; Vincent P. Medjibe; Lee J. T. White; Zewei Miao; Ludovic Banak‐Ngok; Chris Beirne; Connie J. Clark; Aida Cuni‐Sanchez; Mathias Disney; Jean‐Louis Doucet; Michelle E. Lee; Simon L. Lewis; et al. (Global Ecology and Biogeography, 2020)
Aim Large trees [≥ 70 cm diameter at breast height (DBH)] contribute disproportionately to aboveground carbon stock (AGC) across the tropics but may be vulnerable to changing climate and human activities. Here we determine the distribution, drivers and threats to large trees and high carbon forest. Location Central Africa. Time period Current. Major taxa studied Trees. Methods Using Gabon's new National Resource Inventory of 104 field sites, AGC was calculated from 67,466 trees from 578 species and 97 genera. Power and Michaelis–Menten models assessed the contribution of large trees to AGC. Environmental and anthropogenic drivers of AGC, large trees, and stand variables were modelled using Akaike’s information criterion (AIC) weights to calculate average regression coefficients for all p ossible models. Results Mean AGC for trees ≥ 10 cm DBH in Gabonese forestlands was 141.7 Mg C/ha, with averages of 166.6, 171.3 and 96.6 Mg C/ha in old growth, concession and secondary forest. High carbon forests occurred where large trees are most abundant: 31% of AGC was stored in large trees (2.3% of all stems). Human activities largely drove variation in AGC and large trees, but climate and edaphic conditions also determined stand variables (basal area, tree height, wood density, stem density). AGC and large trees increased with distance from human settlements; AGC was 40% lower in secondary than primary and concession forests and 33% higher in protected than non‐managed areas. Main conclusions AGC and large trees were negatively associated with human activities, highlighting the importance of forest management. Redefining large trees as ≥ 50 cm DBH (4.3% more stems) would account for 20% more AGC. This study demonstrates that protecting relatively undisturbed forests can be disproportionately effective in conserving carbon and suggests that including sustainable forestry in programs like reduced emissions for deforestation and forest degradation could maintain carbon dense forests in logging concessions that are a large proportion of remaining Central African forests.

Skin Filling and Firming Activity of a Hyaluronic Acid Inducing Synthetic Tripeptide - Remo Campiche; Eileen Jackson; Guillaume Laurent; Magalie Roche; Sarah Gougeon; Pierre Séroul; Simon Ströbel; Marco Massironi; Mathias Gempeler (International Journal of Peptide Research and Therapeutics, 2020)

Gas Diffusion in Coal Powders is a Multi-rate Process - Simon A. Mathias; Marco Dentz; Qingquan Liu (Transport in Porous Media, 2020)
Gas migration in coal is strongly controlled by surface diffusion of adsorbed gas within the coal matrix. Surface diffusion coefficients are obtained by inverse modelling of transient gas desorption data from powdered coals. The diffusion coefficient is frequently considered to be dependent on time and initial pressure. In this article, it is shown that the pressure dependence can be eliminated by performing a joint inversion of both the diffusion coefficient and adsorption isotherm. A study of the log–log slope of desorbed gas production rate against time reveals that diffusion within the individual coal particles is a multi-rate process. The application of a power-law probability density function of diffusion rates enables the determination of a single gas diffusion coefficient that is constant in both time and initial pressure.

Storage Coefficients and Permeability Functions for Coal-Bed Methane Production Under Uniaxial Strain Conditions - Simon A. Mathias; Stefan Nielsen; Rebecca L. Ward (Transport in Porous Media, 2019)

Ground Data are Essential for Biomass Remote Sensing Missions - Jérôme Chave; Stuart J. Davies; Oliver L. Phillips; Simon L. Lewis; Plinio Sist; Dmitry Schepaschenko; John Armston; Tim R. Baker; David Coomes; Mathias Disney; Laura Duncanson; Bruno Hérault; et al. (Surveys in Geophysics, 2019)

Evaluation of the HadGEM3-A simulations in view of detection and attribution of human influence on extreme events in Europe - Robert Vautard; Nikolaos Christidis; Andrew Ciavarella; Carmen Alvarez-Castro; Omar Bellprat; Bo Christiansen; Ioana Colfescu; Tim Cowan; Francisco Doblas-Reyes; Jonathan Eden; Mathias Hauser; Gabriele Hegerl; et al. (Climate Dynamics, 2019)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Unexpected absence of island endemics: Long‐distance dispersal in higher latitude sub‐Antarctic Siphonaria (Gastropoda: Euthyneura) species - Claudio A. González‐Wevar; Nicolás I. Segovia; Sebastián Rosenfeld; Jaime Ojeda; Mathias Hüne; Javier Naretto; Thomas Saucède; Paul Brickle; Simon Morley; Jean‐Pierre Féral; Hamish G. Spencer; Elie Poulin (Journal of Biogeography, 2018)
Aim We assess biogeographical patterns, population structure and the range of species in the pulmonate genus Siphonaria across the sub‐Antarctic. We hypothesized that locally endemic cryptic species will be found across the distribution of these direct‐developing limpets in the sub‐Antarctic. Location The sub‐Antarctic coasts of the Southern Ocean including South America, the Falkland/Malvinas, South Georgia, Kerguelen and Macquarie Islands. Methods Multi‐locus phylogenetic reconstructions, mt DNA time‐calibrated divergence time estimations and population‐based analyses of Siphonaria populations were used at the scale of the Southern Ocean. Results We resolve two widely distributed lineages of Siphonaria ( S. lateralis and S. fuegiensis ) across the sub‐Antarctic. Mt DNA divergence time estimates suggest that they were separated around 4.0 Ma (3.0 to 8.0 Ma). Subsequently both species followed different evolutionary pathways across their distributions. Low levels of genetic diversity characterize the populations of both species, reflecting the role of Quaternary glacial cycles during their respective demographic histories, suggesting high levels of dispersal among geographically distant localities. Main conclusions Siphonaria lateralis and S. fuegiensis constitute sister and broadly co‐distributed species across the sub‐Antarctic. Unexpected transoceanic similarities and low levels of genetic diversity in both these direct‐developing species imply recurrent recolonization processes through long‐distance dispersal to isolated sub‐Antarctic islands. For such groups of Southern Ocean invertebrates, rafting may be more effective for long‐distance dispersal than a free‐living planktotrophic larval stage. This biogeographical model may explain why many marine species lacking a dispersal phase exhibit broad distributions, low genetic diversity and low population structure over thousands of kilometres.

Mechanisms of hepatotoxicity associated with the monocyclic β-lactam antibiotic BAL30072 - Franziska Paech; Simon Messner; Jochen Spickermann; Mathias Wind; Anne-Hortense Schmitt-Hoffmann; Anne Therese Witschi; Brett A. Howell; Rachel J. Church; Jeff Woodhead; Marc Engelhardt; Stephan Krähenbühl; Martina Maurer (Archives of Toxicology, 2017)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Diversity and community composition of particle‐associated and free‐living bacteria in mesopelagic and bathypelagic Southern Ocean water masses: Evidence of dispersal limitation in the Bransfield Strait - Mathias Milici; Marius Vital; Jürgen Tomasch; Thomas H. Badewien; Helge‐A. Giebel; Iris Plumeier; Hui Wang; Dietmar H. Pieper; Irene Wagner‐Döbler; Meinhard Simon (Limnology and Oceanography, 2017)
The Southern Ocean constitutes about 10% of the global oceans' volume and is characterized by high primary production. Particulate organic matter (POM) is exported from the photic zone to the deep ocean and sustains life of particle associated (PA) and free‐living (FL) bacterial communities in the dark realm. Little is known about the composition and diversity of PA and FL bacterial communities below the photic zone and how they differ among various regions of the Southern Ocean. Therefore, we investigated the composition of small (3–8 μm) and large (> 8 μm) PA and FL (0.2–3 μm) bacterial communities between 500 m and 3600 m in the Bransfield Strait, Drake Passage, and the south Atlantic Ocean featuring also Southern Ocean water masses. PA bacterial communities had a higher OTU richness and evenness than FL ones. Taxonomic analysis revealed a different community composition between FL and PA bacteria. A large number of OTUs belonging to diverse phyla (Bacteroidetes, Planctomycetes, Betaproteobacteria, Deltaproteobacteria, and Verrucomicrobia) were significantly enriched on particles; in contrast very few bacterial lineages were FL specialists. Life‐style (FL vs. PA) and region (Bransfield basin vs. other regions) strongly influenced bacterial communities. Depth explained only marginal fraction of the total variation (∼ 12%), suggesting that selective processes driven by depth have a smaller effect in the Southern Ocean when compared to life‐style (25%) and region (31%). Overall these data indicate a strong influence of isolated water masses such as the basin of the Bransfield Strait on the composition of bacterial communities in the dark ocean.

Large-scale genetic census of an elusive carnivore, the European wildcat (Felis s. silvestris) - Katharina Steyer; Robert H. S. Kraus; Thomas Mölich; Ole Anders; Berardino Cocchiararo; Christiane Frosch; Alexander Geib; Malte Götz; Mathias Herrmann; Karsten Hupe; Annette Kohnen; Matthias Krüger; et al. (Conservation Genetics, 2016)

Simulation of Three-Component Two-Phase Flow in Porous Media Using Method of Lines - Salim Goudarzi; Simon A. Mathias; Jon G. Gluyas (Transport in Porous Media, 2016)

The effect of pH on fatigue during submaximal isometric contractions of the human calf muscle - Jason C. Siegler; Paul Marshall; Mathias K. Pouslen; Niels-Peter B. Nielsen; David Kennedy; Simon Green (European Journal of Applied Physiology, 2015)

A pseudospectral approach to the McWhorter and Sunada equation for two-phase flow in porous media with capillary pressure - Tore I. Bjørnarå; Simon A. Mathias (Computational Geosciences, 2013)

Variable resistance training promotes greater fatigue resistance but not hypertrophy versus constant resistance training - Simon Walker; Juha J. Hulmi; Mathias Wernbom; Kai Nyman; William J. Kraemer; Juha P. Ahtiainen; Keijo Häkkinen (European Journal of Applied Physiology, 2013)

Mammary gland development is delayed in mice deficient for aminopeptidase N - Andreas F. Kolb; David Sorrell; Caroline Lassnig; Simon Lillico; Ailsa Carlisle; Claire Neil; Claire Robinson; Mathias Müller; C. Bruce A. Whitelaw (Transgenic Research, 2013)

Analytical Model for CO2 Injection into Brine Aquifers-Containing Residual CH4 - Seyyed Abolfazl Hosseini; Simon A. Mathias; Farzam Javadpour (Transport in Porous Media, 2012)

Dissolution of CO2 From Leaking Fractures in Saline Formations - Francesca E. Watson; Simon A. Mathias; Jeroen van Hunen; Susie E. Daniels; Richard R. Jones (Transport in Porous Media, 2012)

Analysis of Momentum Transfer in a Lid-Driven Cavity Containing a Brinkman–Forchheimer Medium - Duoxing Yang; Ziqiu Xue; Simon A. Mathias (Transport in Porous Media, 2012)

Pressure Buildup During CO2 Injection into a Closed Brine Aquifer - Simon A. Mathias; Gerardo J. González Martínez de Miguel; Kate E. Thatcher; Robert W. Zimmerman (Transport in Porous Media, 2011)

Hydraulic Fracture Propagation with 3-D Leak-off - Simon A. Mathias; Maarten van Reeuwijk (Transport in Porous Media, 2009)

Approximate Solutions for Pressure Buildup During CO2 Injection in Brine Aquifers - Simon A. Mathias; Paul E. Hardisty; Mark R. Trudell; Robert W. Zimmerman (Transport in Porous Media, 2009)